Lack of tolerable treatment options for patients with schizophrenia - Citrome L; Eramo A; Francois C; Duffy R; Legacy SN; Offord SJ; Krasa HB; Johnston SS; Guiraud-Diawara A; Kamat SA; Rohman P (Neuropsychiatric Disease and Treatment, 2015)
Leslie Citrome,1 Anna Eramo,2 Clement Francois,2 Ruth Duffy,3 Susan N Legacy,3 Steve J Offord,3 Holly B Krasa,3 Stephen S Johnston,4 Alice Guiraud-Diawara,5 Siddhesh A Kamat,3 Patricia Rohman3 1Department of Psychiatry and Behavioral Sciences, New York Medical College, Valhalla, NY, 2Lundbeck, Deerfield, IL, 3Otsuka America Pharmaceuticals, Princeton, NJ, 4Truven Health Analytics, Bethesda, MD, USA; 5Lundbeck SAS, Issy-les-Moulineaux, France Purpose: Atypical antipsychotics (AAs), an effective treatment for schizophrenia, have a range of pharmacologic properties leading to differences in tolerability as well as heterogeneity in treatment response. Individual patient characteristics must be considered when making treatment choices, especially from an adverse event (AE) or tolerability perspective. Despite the availability of numerous AAs, after appraising patient characteristics at the time of treatment selection, physicians may quickly run out of tolerable treatment options. Patients and methods: AE risk factors, defined as having either a prior history of an AE or a risk factor for that AE, were determined for Medicaid-insured and Commercially insured patients using database analysis. Patients receiving AA treatment between January 1, 2010 and December 31, 2012 defined the index date of first observed AA prescription during this period. Nine AAs were evaluated for association with AE risk factors as informed by drug prescribing information from the different manufacturers and published meta-analyses. The proportion of patients with pre-index AE risk factors prescribed an AA associated with that risk factor was then determined. Results: A high proportion of patients (>80%) were prescribed an AA associated with extrapyramidal symptoms or akathisia despite experiencing extrapyramidal symptoms or akathisia prior to AA treatment initiation. Similar trends were observed among patients with diabetes (>60%) and obesity (>40%). From the nine treatment options available, the number of optimal choices for individual patient segments were limited based on their prior history, including those with cardiometabolic and cardiovascular comorbidities (four); experiencing prolactin elevation-related problems (seven); needing to avoid excessive sedation (four); or at risk of extrapyramidal symptoms or akathisia (two). Options were then further restricted among patients in more than one segment when multiple pre-index AE risk factors were combined. Conclusion: When combining patient risk profile with antipsychotic AE profile, physicians may quickly run out of tolerable treatment options for individual patients, despite the availability of many AAs, suggesting a need for additional treatment options with better tolerability and without compromising efficacy. Keywords: schizophrenia, atypical antipsychotics, tolerability, comorbidities, treatment